The analysis of understanding factorial concept processes of 7th grade students who have high academic achievements with pirie-kieren theory - (:unkn) unknown (Sakarya University, 2016)
The aim of this study is to analyze the understanding factorial concept processes of 7th grade students who have high academic achievements with Pirie-Kieren theory. The research participants are composed of two 7th grade students who are studying at a public primary school in the İnegöl district of the city of Bursa. This research has been designed according to case study design since it was carried out with two students who had high academic achievements in a constructive learning environment. The research participants were selected among voluntary students by considering their mathematics achievement test scores and their grades stated in the previous year’ reports. Mathematics achievement test was composed of 15 questions that were covering pre-cognitive knowledge of the factorial concept. Educational games, group work, puzzles, worksheets and activities designed for the objectives in the factorial concept were used in the research. The data of the research was collected by through a semi-structured interview, participant observation and document analysis for each student in the study group. The obtained data was analyzed by using a descriptive analysis method. According to the findings, students who have high academic achievements were able to construct concepts easily by interpreting activities and they reached formalising level according to Pirie and Kieren theory. In the light of the findings of this study, the researchers have developed suggestions. © The Turkish Online Journal of Educational Technology.
Keywords: Factorial; Folding back; Learning to learn; Pirie-Kieren theory